High-throughput ß-galactosidase and ß-glucuronidase Assays Using Fluorogenic Substrates - Ramsay, Joshua (2013)
β-galactosidase and β-glucuronidase enzymes are commonly used as reporters for gene expression from gene promoter-lacZ or uidA fusions (respectively). The protocol described here is a high-throughput alternative to the commonly used Miller assay (Miller, 1972) that utilises a fluorogenic substrate (Fiksdal et al., 1994) and 96-well plate format. The fluorogenic substrates 4-Methylumbelliferyl β-D-galactoside (for β-galactosidase assays) (Ramsay et al., 2013) or 4-Methylumbelliferyl β-D-glucuronide (for β-glucuronidase assays) (Ramsay et al., 2011) are cleaved to produce the fluorescent product 4-methylumbelliferone. Cells are permeabilized by freeze-thawing and lysozyme, and the production of 4-methylumbelliferone is monitored continuously by a fluorescence microplate reader as a kinetic assay. The rate of increase in fluorescence is then calculated, from which relative gene-expression levels are extrapolated. Due to the high sensitivity fluorescence-based detection of 4-methylumbelliferone and the high density of time points collected, this assay may offer increased accuracy in the quantification of low-level gene expression. The assay requires small sample volumes and minimal preparation time. The permeabilisation conditions outlined in this protocol have been optimised for Gram-negative bacteria (specifically Escherichia coli and Serratia), but is likely suitable for other organisms with minimal optimisation.